CAO NGUYÊN ĐÁ ĐỒNG VĂN - CÔNG VIÊN ĐỊA CHẤT TOÀN CẦU ĐẦU TIÊN CỦA VIỆT NAM VÀ VẤN ĐỀ BẢO TỒN DI SẢN ĐỊA CHẤT - Phúc, La Thế; Văn, Trần Tân; Tuất, Lương Thị; Anh, Đoàn Thế; Chung, Hồ Tiến; Huyên, Đặng Trần; Khiển, Nguyễn Xuân; Ngọc, Đàm; Ngọc, Đỗ Thị Yến; Trung, Nguyễn Đại; et al. (Vietnam Journal of Earth Sciences, 2011)
Dong Van rock highland - the first international Geopark of Vietnam and geoheritage preservation Dong Van Karst Plateau has the richness and diversity in geoheritages. Initial research conducted by Vietnamese and foreign geologists highlighted five types of geological heritages (according to UNESCO classification): type Apalaeogeology, type B- geomorphology, type D- rock, type E-stratigraphy, type I-tectonics. Besides geoheritages, the biodiversity and the historical, cultural and societal richness of Dong Van Karst Plateau (which met UNESCO criteria of a global geopark), has made it recognised as a member of global Geopark Network by UNESCO for the years 2010 - 2014. The management, conservation and rational exploitation of heritages (especially geoheritages) should be raised seriously and given priority in every economic development strategy of the local government, in order to maitain its honourable title and enhance the sustainable socio-economic development. This paper introduce some main features of Dong Van Karst Plateau Geopark, the event of the UNESCO rewarding Dong Van Karst Plateau with the title “Global Geopark” and the issues of preservation of its local geoheritages.